Breast cancer incidence and mortality - trends from 1990 to 2019 and projections for 2020 to 2029 in the world female population: a GBD 2019 data-based analysis - Tongzhou GAN; Kongjun YUAN; Danhong YAN; Guangqing ZHOU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the trends in breast cancer incidence and mortality from 1990 to 2019 and to predict the age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) of breast cancer from 2020 to 2029 in the world female population, providing a reference for the prevention and control of female breast cancer in the world. MethodsData on breast cancer incidence and mortality in the global female population from 1990 to 2019 were collected from the Global Burden of Disease (GBD) 2019 study. Incidence count, incidence rate, ASIR, death count, mortality rate, and ASMR were used for descriptive analysis. Average annual percentage change (AAPC) was used to analyze trends in breast cancer incidence and mortality from 1990 to 2019. The age-period-cohort (APC) model was used to estimate the age effect, period effect, and cohort effect on breast cancer incidence and mortality risk in the world female population; the autoregressive integrated moving average (ARIMA) model was used to predict trends in breast cancer incidence and mortality from 2020 to 2029 in the female population. ResultsIncreases in breast cancer in the global female population from 1990 to 2019 were observed in incidence number (867 620.84 to 1 977 211.62), incidence rate (32.67/100 000 to 51.27/100 000), ASIR (40.12/100 000 to 45. 86/100 000), number of deaths (375 016.06 to 688 562.26), and mortality rate (14.12/100 000 to 17.85/100 000), with total percentage changes of 127.89%, 56.93%, 14.31%, 83.61%, and 26.42%, respectively. The breast cancer ASMR decreased from 17.76/100 000 in 1990 to 15.88/100 000 in 2019, with an overall percentage change of - 10.54%. Joinpoint regression analysis showed that breast cancer ASIR for the global female population generally increased from 1990 to 2019 (AAPC = 0.44, P < 0.001), while breast cancer ASMR generally decreased (AAPC = - 0.37, P < 0.001). Trends in female breast cancer incidence and mortality varied across global regions with different levels of socio-demographic index (SDI) from 1990 to 2019. The ASIR generally increased in global regions with different SDI levels. The ASMR generally increased in the middle, low-middle, and low SDI regions, but generally decreased in the high and high-middle SDI regions from 1990 to 2019 (all P < 0.001). The APC model analysis showed that the age effects on breast cancer incidence and mortality rates in the global female population generally increased with age, with coefficients increasing from - 2.878 and - 2.946 at ages 20 - 24 years to 0.706 and 1.053 at ages 75 - 79 years, respectively. Period effects on breast cancer incidence and mortality also showed increasing trends, with coefficients increasing from - 0.310 and - 0.206 in 1990 - 1994 to 0.296 and 0.235 in 2015 - 2019, respectively. However, cohort effects on breast cancer incidence and mortality generally decreased, with coefficients decreasing from 0.848 and 0.866 for the 1915 - 1919 birth cohort to - 0.575 and - 0.672 for the 1995 - 1999 birth cohort, respectively. ARIMA model predictions showed that the global female breast cancer ASIR will continue to increase while the ASMR will continue to decrease from 2020 to 2029, with predicted ASIR and ASMR of 47.86/100 000 and 15.31/100 000, respectively, in 2029. ConclusionFrom 1990 to 2019, the ASIR for breast cancer has generally increased while the ASMR has generally decreased in the global female population. From 2020 to 2029, the ASIR is projected to continue to increase while the ASMR is projected to continue to decrease.